Mapping Deprivations in Mauritania - Dahmani-Scuitti, Anais; Doyle, Jesse; Lefebvre, Matthieu; Meyer, Moritz; Rajashekar, Anirudh (World Bank, Washington, DC, 2020)
Recent economic growth In Mauritania has helped reduce poverty, but spatial disparities in terms of both monetary welfare and access to services and opportunities remain. Designing policies and projects to improve living conditions requires localized and updated data not usually available from household surveys. Deprivation mapping—a new spatial deprivation analysis tool—uses administrative and geospatial settlement-level data (the lowest administrative unit in our case study Mauritania) to estimate settlement access deprivations across 4 dimensions: social services, basic infrastructure, opportunities, and exposure to weather/climate shocks. Database and visualizations (map) highlight and rank each settlement’s deprivation index, enhancing national data and showing spatial differences in the depth, complexity, and persistence of deprivations to inform policies and prioritize investments.